The anterior sylvian point as a reliable landmark for the anterior temporal lobectomy in mesial temporal lobe epilepsy: technical note, case series, and cadaveric dissection - Fava, Arianna; Lisi, Serena Vittoria; Mauro, Luigi; Morace, Roberta; Ciavarro, Marco; Gorgoglione, Nicola; Petrella, Giandomenico; Quarato, Pier Paolo; Di Gennaro, Giancarlo; di Russo, Paolo; Esposito, Vincenzo (Frontiers in Medicine, 2024)
Introduction Mesial temporal lobe epilepsy (MTLE) is one of the most prevalent forms of focal epilepsy in surgical series, particularly among adults. Over the decades, different surgical strategies have been developed to address drug-resistant epilepsy while safeguarding neurological and cognitive functions. Among these strategies, anterior temporal lobectomy (ATL), involving the removal of the temporal pole and mesial temporal structures, has emerged as a widely employed technique. Numerous modifications have been proposed to mitigate the risks associated with aphasia, cognitive issues, and visual field defects. Methods Our approach is elucidated through intraoperative and cadaveric dissections, complemented by neuroradiological and cadaveric measurements of key anatomical landmarks. A retrospective analysis of patients with drug-resistant MTLE who were treated using our ATL technique at IRCCS Neuromed (Pozzilli) is presented. Results A total of 385 patients were treated with our ATL subpial technique anatomically focused on the anterior Sylvian point (ASyP). The mean FU was 9.9 ± 5.4 years (range 1–24). In total, 84%of patients were free of seizures during the last follow-up, with no permanent neurological deficits. Transient defects were as follows: aphasia in 3% of patients, visual field defects in 2% of patients, hemiparesis in 2% of patients, and cognitive/memory impairments in 0.8% of patients. In cadaveric dissections, the ASyP was found at a mean distance from the temporal pole of 3.4 ± 0.2 cm (range 3–3.8) at the right side and 3.5 ± 0.2 cm (3.2–3.9) at the left side. In neuroimaging, the ASyP resulted anterior to the temporal horn tip in all cases at a mean distance of 3.2 ± 0.3 mm (range 2.7–3.6) at the right side and 3.5 ± 0.4 mm (range 2.8–3.8) at the left side. Discussion To the best of our knowledge, this study first introduces the ASyP as a reliable and reproducible cortical landmark to perform the ATL to overcome the patients’ variabilities, the risk of Meyer’s loop injury, and the bias of intraoperative measurements. Our findings demonstrate that ASyP can be a safe cortical landmark that is useful in MTLE surgery because it is constantly present and is anterior to risky temporal regions such as temporal horn and language networks.